Realistic simulation in teaching nursing practices in wound care: Account of experiences (Research, Society and Development, 2021)
Objective: report the experience of the teaching staff of the nursing technical course of an application college in the west of Rio de Janeiro using realistic simulation as a methodology for teaching and learning for middle school students, We used as a method010kv; the experience report on the use of realistic simulation, since it allows the students involved in the practice to experience existing roles in real life, adapting their posture and professional performance according to the presented case, the resources and their perception of the health environment. Main results: The students of the class improve their knowledge by realistically having their knowledge exemplified and through this dynamic allowed students from other classes, periods and professional courses, as well as family members and other members of the faculty of the institution understood the healing process, the approach of the lesions and therapeutics to be used in each type of wound, spreading the knowledge among all Conclusions: Many health care courses have used the realistic simulation in their process of training new professionals, however, there is still little research evidencing the need for new studies to foster the effectiveness of this teaching.